A critical review of the evidence for nurses as information providers to cancer patients - Papathanassoglou, Elizabeth; Koutsopoulou, Sotiria; Katapodi, Maria (My University, 2010)
Aims: To review evidence on the role of oncology nurses in the provision of information to cancer patients and to delineate evidence-based implications for clinical practice and research. Background: Provision of information is central for the empowerment of patients to participate in their care. There is not enough evidence regarding the nursing role in the information delivery process in cancer patients. Design: Descriptive literature review. Methods: From January 1990-2008, databases searched included Medline, CINAHL, PubMed, CancerLit and the Cochrane Library. Original research articles addressing the role of nurses in information delivery were included. We explored evidence on: (1) the effectiveness of nurses as information providers, (2) the way patients evaluate nurses' input to information delivery, (3) the extent to which nurses contribute to information delivery to cancer patients and (4) the types of information provided by nurses. Results: The most important findings were: (1) nurses' role as information providers for cancer patients is prominent, especially after the initiation of treatment, (2) specialist nurses are very effective in providing information, (3) no clear evidence exists on how nurses compare with other health-care professionals as information providers and (4) some evidence exists that patients may prefer nurses as information providers at specific times in their treatment and especially in regards to symptom management. Conclusion: Well-designed studies provide some evidence that nurses are effective as information providers to cancer patients. Specifically, oncology nurses are able to provide information of both high quality and of appropriate quantity and to assist individuals to interpret information provided by others. Relevance to clinical practice: Oncology nurses should be specifically educated and prepared to offer explicit, practical and timely information and they should be trained in interpersonal communication skills, which will increase their ability to comprehend patient information needs
Keywords: Nurse; Cancer; Oncology; Critical review; Information delivery; Information provider